2019
DOI: 10.1016/j.jjcc.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding and ischemic events during dual antiplatelet therapy after second-generation drug-eluting stent implantation in hemodialysis patients

Abstract: Background: Dual-antiplatelet therapy (DAPT) after second-generation drug-eluting stent (2nd-DES) implantation reduces the risk of stent thrombosis and subsequent ischemic events, with an increase in bleeding risk. Although chronic kidney disease patients have both high ischemic and bleeding events, little is known about both risks during DAPT in hemodialysis (HD) patients. Methods: From July 2009 to March 2017, we retrospectively analyzed bleeding events and major adverse cardiac and cerebrovascular events (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In contrast, the 1-year event rate for patients with preserved renal function was comparable to that in other recently published studies evaluating the safety and performance of new-generation DES indicating good performance of the Ultimaster stent. The prospective COMBO Stent registry, for instance, included 3614 patients and documented TLF in 3.9%, cardiac death in 1.6%, and definite stent thrombosis in 0.5% (versus 3.3%, 1.4%, and 0.4% herein) [25][26][27][28][29][30]. Although complication rates were relatively low in general, patients with CKD had a higher risk of major and minor bleeding as well as access site-related complications leading to prolonged hospitalization and higher rates of end points at discharge (supplement Table 1), which is in line with previous publications [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the 1-year event rate for patients with preserved renal function was comparable to that in other recently published studies evaluating the safety and performance of new-generation DES indicating good performance of the Ultimaster stent. The prospective COMBO Stent registry, for instance, included 3614 patients and documented TLF in 3.9%, cardiac death in 1.6%, and definite stent thrombosis in 0.5% (versus 3.3%, 1.4%, and 0.4% herein) [25][26][27][28][29][30]. Although complication rates were relatively low in general, patients with CKD had a higher risk of major and minor bleeding as well as access site-related complications leading to prolonged hospitalization and higher rates of end points at discharge (supplement Table 1), which is in line with previous publications [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the potential disadvantage of low response to thienopyridine was observed in HD patients [ 17 ]. Furthermore, a previous study reported that dialysis patients who underwent PCI with DES implantation showed more adverse bleeding events compared with non-dialysis patients [ 4 ]. In another study, prolonged dual antiplatelet therapy (DAPT) in dialysis patients after DES implantation reduced MACE without significantly increasing major bleeding [ 18 ]; thus, the duration of DAPT after DES implantation in dialysis patients is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on dialysis tend to have complex coronary artery lesions, such as massive calcification, which may lead to an increased risk of in-stent restenosis (ISR) [ 3 ]. Moreover, patients undergoing dialysis after PCI with new-generation DES have more adverse bleeding events [ 4 ]. Drug-coated balloon (DCB) angioplasty is a well-known, effective, and safe treatment for de novo lesions in coronary arteries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, it is estimated that hemodialysis is performed in nearly 89% of kidney failure patients, and its application assists in improving the survival of these patients to some extent (Himmelfarb et al 2020;Ng et al 2022;Thurlow et al 2021). Unfortunately, major adverse cardiac and cerebrovascular events (MACCE) (including acute coronary syndrome, heart failure, cardiac death, and stroke) frequently occur in patients receiving hemodialysis, and the incidence of MACCE within 2 years in these patients ranges from 10.3% to 36.7% (Kim et al 2015;Lee et al 2014;Shimizu et al 2019;Stirnadel-Farrant et al 2019). Under this situation, exploring potential markers that predict MACCE might be meaningful to improve the management of patients receiving hemodialysis.…”
Section: Introductionmentioning
confidence: 99%